The Strategy of Business Performance Development for UPPKS in Facing the Demographic Bonus Era - Wyati Saddewisasi; Surjawati; Aprih Santoso (Quantitative Economics and Management Studies, 2022)
The basic problems faced by UPPKS in Semarang are as follows (Jateng Pos, 2019): 1) Many group businesses do not develop and "die" in the middle of the process, 2) They do not have information on forms and access to capital, 3) They have not been able to manage the existing UPPKS capital, 4) Management has not been able to run the organization well, 5) The group has an organizational structure but does not have activities, 6) Business activities are still independent and not well organized. Thus, the existing UPPKS is not functioning properly. However, the UPPKS is expected to create jobs, especially in the era of the demographic bonus. The UPPKS problems can fail to capture the demographic bonus because it has not been able to develop its members' businesses. This can result in people not being attracted to become members of the UPPKS. Specifically, this study aims to describe: 1) the strategic factors that exist in UPPKS in facing the demographic bonus era 2) the potential for developing business performance in facing the demographic bonus 3) the strategies of business performance development for UPPKS in facing the demographic bonus. This study used the descriptive exploratory approach by analyzing the UPPKS performance strategy. This study is the survey at the UPPKS in Semarang. The population of this study is the management of the UPPKS group in Semarang. The UPPKS sample was determined by purposive sampling. The number of samples of UPPKS management is 16 people representing 16 sub-districts in Semarang. The steps taken in this study are as follows: 1) identifying the strategic factors related to the development of UPPKS performance, 2) factors will be analyzed by using SWOT analysis. The attributes used in the questionnaire were obtained from the perceptions of stakeholders and UPPKS, which in general included attributes of internal conditions consisting of strengths and weaknesses as well as external conditions of UPPKS, which consisted of opportunities and threats. This study produced output in the form of the performance development strategy at UPPKS, namely growth with concentration through horizontal integration.